PENILAIAN TINGKAT REKRUTMEN KARANG KERAS (SCLERACTINIA) DI TAMAN LAUT PANDANAN, LOMBOK UTARA, NUSA TENGGARA BARAT UNTUK MENDUKUNG UPAYA RESTORASI - Ian Rico Andreas Ricardo; Muhammad Farhan Anshory; Citra Satrya Utama Dewi (LPSDI Bina Patria, 2024)
Pandanan Marine Technopark has a flat topography in the middle, and hills on the southwest and northeast sides. Based on a survey using the manta tow method that has been carried out by researchers in 2021, the sea water conditions are clear but the coral reefs are not good. One of the factors suspected to be the cause of the poor condition of the coral reefs in Pandanan Marine Technoark is that many fishermen used to use bombs to catch fish. One of the efforts made by the government and the local (POKMASWAS) to restore the coral reef ecosystem in the Pandanan Marine Technopark is by creating a program to restore corals asexually using coral transplant media. Until now, no research has been conducted in Pandanan Marine Technopark on the sexual recovery of coral reef ecosystems using a coral recruitment level approach.Coral reefs are a group of zooxanthellae symbiotic animals that are very vulnerable to environmental changes. Meanwhile, coral recruitment is a process in which new individual corals are formed through coral reproduction and then join the coral community by forming new colonies. The method used in this study is Underwater Photo Transect (UPT) method and quantitative analysis method consisting of analysis of coral recruitment data for identification of coral recruitment genus, diversity index, uniformity index and dominance index. The results of the recruitment rate for hard corals (Scleractinia) in Pandanan Marine Technopark showed that the recruitment results were based on the lifeforms found including branching, massive, and free living. Meanwhile, the substrate that recruited coral grows the most is Dead Coral with Algae. There were 7 genus found which included Acropora, Favia, Montastrea, Stylophora, Pocilopora, Leptastrea, and Fungia. Most coral recruitment was found at Station 1 with a depth of 3 meters and the lowest number was at Station 3 with a depth of 3 meters. The average Diversity Index is 1.08, which means that the diversity is relatively small and the ecological pressure is very strong. The average uniformity index was 0.91 which means high uniformity and stable community. Furthermore, the average Dominance Index is 0.51, which means moderate dominance